2023
DOI: 10.1063/5.0144795
|View full text |Cite
|
Sign up to set email alerts
|

Untrained deep network powered with explicit denoiser for phase recovery in inline holography

Abstract: Single-shot reconstruction of the inline hologram is highly desirable as a cost-effective and portable imaging modality in resource-constrained environments. However, the twin image artifacts, caused by the propagation of the conjugated wavefront with missing phase information, contaminate the reconstruction. Existing end-to-end deep learning-based methods require massive training data pairs with environmental and system stability, which is very difficult to achieve. Recently proposed deep image prior (DIP) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Augmenting the number of images may enhance result accuracy but at the expense of increased measurement time. Notably, unlike TIE, DIHM has the potential for single-shot implementation 21 . Secondly, DIHM, being an interference technique, necessitates a coherent light source.…”
Section: Methodsmentioning
confidence: 99%
“…Augmenting the number of images may enhance result accuracy but at the expense of increased measurement time. Notably, unlike TIE, DIHM has the potential for single-shot implementation 21 . Secondly, DIHM, being an interference technique, necessitates a coherent light source.…”
Section: Methodsmentioning
confidence: 99%
“…: 1–180 (input only) l 2 -norm with aperture constraint and physical model Bai et al 154 Hologram dual-wavelength Phase CDD Expt. : 1 (input only) l 2 -norm with physical model Galande et al 155 Hologram Phase and amplitude U-Net Expt. : 1 (input only) l 2 -norm with physical model and denoiser Yao et al 159 3D diffraction image Phase and amplitude 3D Y-Net Sim.…”
Section: Dl-in-processing For Phase Recoverymentioning
confidence: 99%
“…Meanwhile, Bai et al 154 extended this from a single-wavelength case to a dual-wavelength case. Galande et al 155 found that this way of neural network optimization with a single-measurement intensity input lacks information diversity and can easily lead to overfitting of the noise, which can be mitigated by introducing an explicit denoiser. It is worth pointing out that this way of using the object-related intensity image as the neural network input makes it possible to internalize the mapping relationship between intensity and phase into the neural network through pre-training .…”
Section: Dl-in-processing For Phase Recoverymentioning
confidence: 99%
“…CNNs can be used for hologram generation [20][21][22] and reconstruction, including noise, twin image and zero-order suppression [23]. CNNs are typically used to reconstruct one image [24][25][26][27][28][29][30][31][32] or two (amplitude and phase information) [33][34][35][36][37][38][39][40][41] or extended focus imaging [41,42]. However, the direct reconstruction of the entire 3D-scene provides a wider range of possibilities [43].…”
Section: Introductionmentioning
confidence: 99%